Community health education improves child health care in Rural Western China - Weifeng Liang; Yuan Xing; Miaomiao Pang; Duolao Wang; Hong Yan (BMC Pediatrics, 2018)
Abstract Background Rural infant growth failure has been highlighted as a priority for action in China’s national nutrition and child development policies. The aim of this paper was to evaluate the effect of community-based intervention project on child feeding, child health care and child growth. Methods From 2001 to 2005, UNICEF and China’s Ministry of Health worked together to develop holistic strategies for child health care. All the interventions were implemented through the three-tier (county-township-village) rural health care network.In this study, 34 counties were included in both surveys in 2001 and 2005. Among these 34 counties, nine were subjected to the intervention and 25 counties were used as controls. In nine intervention counties, leaflets containing information of supplemental feeding of infants and young children were printed and distributed to women during hospital delivery or visit to newborn by village doctors. Two cross-sectional surveys were both conducted from July to early September in 2001 and 2005. We calculated Z-scores of height-for-age (HAZ), weight-for-age (WAZ) and weight-for-height (WHZ), with the new WHO growth standard. HAZ < − 2 was defined as stunting, WAZ < − 2 was defined as underweight, and WHZ < − 2 was defined as wasting. Results Following the four-year study period, the parents in the intervention group showed significantly better infant and young child feeding practices and behaviors of child care than did their control group counterparts. In addition, all three anthropometric indicators in 2005 in the intervention group were better than in the control, with stunting 4.9% lower (p < 0.001), underweight 2.2% lower (p < 0.001), and wasting 1.0% lower (p < 0.05). Conclusions We concluded that the health care education intervention embed in government had the potential to be successfully promoted in rural western China.